Cercle Graphique Européen. (Utrecht : Cercle Graphique Européen, 1971)
Antes, Horst ; Bazaine, Jean ; Corneille ; Kokoschka, Oskar ; Vasarely, Victor ; Vieira da Silva ; Alechinsky, Pierre ; Hartung, Hans ; Moore, henry ; Saura, Antonio ; Sutherland, Graham ; van Velde, Bram
Frans & Engels & Duits
boek